Boycotted, and Other Stories - Reed, Talbot Baines, 1852-1893 (Salt Lake City, UT : Project Gutenberg, 2007)
"Boycotted, and Other Stories" by Talbot Baines Reed is a collection of short stories likely written in the late 19th century. The stories explore the life and experiences of boys at a school, capturing their adventures, friendships, and conflicts. The primary narrative in the opening, titled "Boycotted," centers around a boy named Smither who is grappling with the sudden expulsion of his friend Browne and the subsequent ostracism he faces from his peers. At the start of the book, Smither reflects on the impact of Browne's expulsion from Draven's school, feeling a mixture of confusion and loyalty. The atmosphere at school is somber as Smither's friends distance themselves from him without explanation. As he navigates the isolation and attempts to understand his social standing, he discovers that he has been boycotted due to a misunderstanding regarding his perceived betrayal of Browne. The beginning sets the stage for a rich exploration of themes such as friendship, integrity, and the struggles of adolescence against the backdrop of school life. (This is an automatically generated summary.)
Release date is 2007-04-12
Produced by Nick Hodson of London, England
Keywords: Short stories; Schools -- Fiction